PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN GENERASI MILENIAL DI JAKARTA SELATAN - Sania Azhari; Nyoman Suprastha; Chaerani Nisa Nisa (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
This study aims to examine the effect of work discipline and motivation on job satisfaction of millennial generation employees in South Jakarta. The sample of this study used 100 respondents using primary data sources from the results of filling out questionnaires. The data analysis method uses PLS (Partial Least Square) analysis techniques through SmartPLS 3.0 software. The results obtained from this study show that Work Discipline has a positive and significant effect on Employee Job Satisfaction. Then the Motivation variable has a positive and significant effect on Employee Job Satisfaction. Based on simultaneous R-square measurements, Work Discipline and Motivation have a significant effect on Millennial Generation Employee Job Satisfaction in South Jakarta.